SYSTEMATIC ANALYSIS AND LIST OF SPIDER SPECIES DISTRIBUTED IN CENTRAL FERGANA AREA (Scientific journal of the Fergana State University, 2024)
The purpose of the study is to study the diversity of the arachnofauna of Central Ferghana and to analyze the area of distribution in the region. The article presents the results of observations and research conducted in 2023-2024 in Yazyavan, Altyaryk, Tashlak, Qushtepa, Bahdad, Rishtan, Mingbulak, Ulugnor districts of the Central Fergana region in order to study the arachnofauna of Central Fergana. We inform you that 13 species belonging to 9 families and 11 genera were identified as a result of the research. The systematic position of the identified species was compared with the data of identifiers, international databases and the results of arachnofaunistic observations of other researchers. The morphology of the species was studied and morphological characters were presented. A list of species recorded in the area was compiled and coordinates were obtained.